Did States With More Social Capital Pre-pandemic Offer Mental Health Protection During the COVID-19 Pandemic? A Cross-Sectional View - Dauner, Kim Nichols; Wilmot, Neil A. (Frontiers in Public Health, 2022)
Background: Social capital is a well-known health determinant with both relational and geographic aspects. It can help mitigate adverse events and has been shown to impact behaviors and responses during the COVID-19 pandemic. Mental health has declined during the COVID-19 pandemic, and social capital, may serve to buffer those declines. Methods: Building from this, we assessed whether pre-pandemic social capital and contemporaneous social policy, which included indicators of social trust, civic participation, and presence of mask mandates, affected pandemic mental health, measured as the percent of the population experiencing symptoms of depression and anxiety at the state level. Results: Generalized social trust and state mask mandates were significantly associated with lower levels of depression and anxiety. Conversely, states with greater civic engagement prior to the pandemic experienced more anxiety and depression. Conclusions: Findings suggest that existing social capital, particularly social trust, may protect against anxiety and depression and contribute to community resilience during times of adversity. States should invest in policies and programs that increase social trust.